Design and Development of a Website-Based Power Bank Rental Monitoring System Using a Framework and Blackbox Testing Method - Rahman, Randa; Ritzkal, Ritzkal; Kusumah, Fitrah Satrya Fajar (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This research shows that in today's digital era, users of electronic devices such as smartphones often experience difficulties in managing their battery power needs, especially when using power banks. Uncertainty in the availability and maintenance of power bank rentals can cause inconvenience to users. Therefore, a system is needed that can facilitate the process of renting and managing power banks. This research aims to design a website-based power bank rental monitoring system. The methods used in this research include a framework for designing the system and testing using black-box testing to ensure application functionality. System development was conducted through five stages: planning, analysis, design, implementation, and testing. RFID technology was applied to facilitate the payment process, while Wi-Fi was used for interaction between the user and the application. The features in the system include dashboard, member data, power bank data, and transaction data, which are designed to make it easier for administrators to manage rental data. The research shows that the developed application successfully simplifies the process of purchasing, paying, and returning power banks with easily accessible features and timely notifications. This application not only provides a practical solution for users in managing power bank rentals, but also helps admins in handling transactions and generating reports. Thus, this system is expected to fulfill users' needs for battery power more efficiently.